Business dimensions of EU's new FTAs. Issue 7 (10th November 2017) - Pelkmans, Jacques
Abstract: Recent Free Trade Area (FTA) agreements of the EU are 'deep and comprehensive'. This can be explained by the various and complex 'trading costs' that business encounters when accessing a foreign market and which business is keen to reduce as much as possible. The paper examines what 'deep and comprehensive' means more precisely in four EU FTAs: CETA and EU/Korea, and two FTAs that have not yet been completed (TTIP and EU/Japan). It provides a tentative explanation of the nature of these four modern EU FTAs by taking a closer look at the business dimension, in particular transnational value chains in some prominent sectors, the growing importance of services and inter-sectoral linkages.